1979
DOI: 10.1055/s-0028-1095806
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin does not Cause Sustained Fasting Hyperglycemia in Man

Abstract: Sumatustatin inhibits buth insulin and glucagon secretion (Gerich, Lovinger and Grodsky (1975); its short-term infusion causes a transient decrease in plasma glucose followed by modest hyperglycemia in man (Lins and Efendic 1976; Sherwin. Hendler. DeFronzo. Wahren and Felig 1977), suggesting that insulin deficiency per se is sufficient to cause fasting hyperglycl'mia. If this is true, then prolonged inhibition of insulin secretion should result in persistent and more progressive hyperglycemia. On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Furthermore, a functional study on isolated human islet cells confirmed the importance of the sstr 5 receptor for insulin secretion (Zambre et al 1999). In studies on healthy human subjects, infusion of natural somatostatin results in a transient increase in glucose for about 6 h, despite a sustained suppression of insulin and glucagon (Rizza et al 1979).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, a functional study on isolated human islet cells confirmed the importance of the sstr 5 receptor for insulin secretion (Zambre et al 1999). In studies on healthy human subjects, infusion of natural somatostatin results in a transient increase in glucose for about 6 h, despite a sustained suppression of insulin and glucagon (Rizza et al 1979).…”
Section: Discussionmentioning
confidence: 98%
“…In these experiments, replacement glucagon doses of ~7 ng/kg-min resulted in glucagon plasma concentrations of ~40 to 60 pg/ml and relatively small increases in the glucagon infusion rates could result in a rise in blood glucose concentrations. 36,42,55 In addition, we rationalized that since subcutaneous insulin pump infusion was effective in controlling the plasma glucose 56-58 a similar argument could be made for glucagon.…”
Section: Mini-dose Glucagonmentioning
confidence: 99%
“…Indeed, although plasma glucose concentrations have been observed to increase above fasting levels during somatostatin infusion (5,6), a 12-h somatostatin infusion did not cause sustained fasting hyperglycemia (24). Thus, in the short-term, factors in addition to these hormones must be involved in maintenance of the postabsorptive glucose level.…”
Section: Discussionmentioning
confidence: 99%